Can delaying germination reduce barriers to successful emergence for early‐germinating, fall‐sown native bunchgrass seeds in cold deserts?. Issue 2 (10th August 2022) - Baughman, Owen W.; Kerby, Jay D.; Boyd, Chad S.; Madsen, Matthew D.; Svejcar, Tony J.
Abstract : Efforts to restore semiarid wildlands in the western United States predominantly use fall seeding. Fall conditions are more amenable to seeding, and successfully over‐wintered seeds or plants are poised to take full advantage of spring moisture. However, over‐winter mortality can be a barrier to seeding success. One solution to avoid winter mortality without sacrificing the benefits of fall seeding is to delay germination of fall‐sown seeds. At six northern Great Basin field sites over three planting years (18 trials), we tested whether a hydrophobic seed coating reliably delayed germination and increased seedling establishment of a native bunchgrass. Despite considerable variation among sites and years, seed treatment successfully reduced pre‐winter germination by 84% compared to untreated, but also consistently reduced final germination by 23%. Still, treatment resulted in an average of 2.1‐fold higher emerged seedling density in seven trials, six of which were among the eight trials where more than 50% of untreated seeds germinated pre‐winter. Emergence was greater for untreated seed in five trials, all of them in the same year, and all but one of them with below‐average total germination. Our treatment consistently reduced pre‐winter germination, but only improved emergence when pre‐winter germination of untreated seeds was high. Continued research is merited with germination‐delaying treatments and to experimentally define—and develop models that predict—winter‐related mortality barriers. We also suggest future exploration of bet‐hedging strategies that mix treated and untreated seeds where fall seeding is required and significant but variable risk of over‐winter seedling mortality exists.